Preliminary Assessment of Dietary Mannanoligosaccharides on Growth Performance and Health Status of Gilthead SeabreamSparus auratus - Tanrıkul, Tevfik Tansel; Salnur, Semih; Aydın, Seyit; Hi̇sar, Olcay; Gültepe, Nejdet; Hoşsu, Belgin (Oxford University Press (OUP), 2012)
AbstractA feeding trial was performed to assess the potential beneficial effect of two levels of mannanoligosaccarides (MOS) on the growth performance, feed utilization, hematological parameters, and liver histopathology of gilthead seabream Sparus auratus (also known as gilthead bream). Mannanoligosaccarides were added at the rates of 2 and 4 g/kg to a fish-meal-based control diet, and each diet was given (twice daily [midmorning and midafternoon] to apparent satiation) to triplicate groups of gilthead seabream growers (mean weight = approximately 170 g) in sea cages. The trial lasted 12 weeks, and the average ambient water temperature ranged from 19.6°C to 24.7°C during the experimental period. At the end of the experiment, fish attained market size (350–450 g) and their health status was evaluated by blood analysis and liver histology. There were no differences in survival rates among fish fed experimental diets. However, there were significant improvements in both growth and feed utilization among fish fed diets supplemented with MOS. Hemoglobin (Hb) and hematocrit (Ht) levels and erythrocyte, leukocyte, and thrombocyte (Thr) counts were unaffected by any dietary MOS. The levels of Hb (g/dL; mean ± SD) and Ht (%; mean ± SD) were 11.0 ± 2.5 and 45.6 ± 6.7 for the control group, 11.1 ± 1.7 and 39.3 ± 8.0 for the 2-g/kg group, and 11.2 ± 1.9 and 40.2 ± 8.4 for the 4-g/kg group. The mean Thr count ranged from 47.6 to 53.8 × 103/mm3. Despite the apparently higher Thr counts for fish fed diets supplemented with MOS, these differences were not significant. Moreover, no histopathological differences were observed in liver tissue cross sections between control and treatment groups. These results suggest that supplementation of diets with MOS had no significant effects on general fish health.Received February 20, 2011; accepted September 12, 2011
Keywords: Mannans; Dose-Response Relationship, Drug; Dietary Supplements; Animals; Animal Nutritional Physiological Phenomena; Animal Feed; Sea Bream; Diet; 2. Zero hunger